Relationship between aortic wall oxidative stress/proteolytic enzyme expression and intraluminal thrombus thickness indicates a novel pathomechanism in the progression of human abdominal aortic aneurysm. Issue 1 (23rd October 2018) - Wiernicki, Ireneusz; Parafiniuk, Miroslaw; Kolasa-Wołosiuk, Agnieszka; Gutowska, Izabela; Kazimierczak, Arkadiusz; Clark, Jeremy; Baranowska-Bosiacka, Irena; Szumilowicz, Pawel; Gutowski, Piotr
ABSTRACT: The possibility that oxidative stress promotes degradation of the extracellular matrix and a relationship between intraluminal thrombus (ILT) thickness and proteolytic activity within the abdominal aortic aneurysm (AAA) wall has been suggested. In the present study, the hypothesis that thin ILT is correlated with an increase in oxidative stress–related enzymes and matrix metalloproteinase‐9 (MMP‐9) expression within the human AAA wall was investigated. We also studied the antioxidant activity of superoxide dismutases, catalase, glutathione peroxidase, glutathione reductase, and thioredoxin within the full‐thickness AAA wall and through fluoroimmunohistochemical staining of catalase and MMP‐9 expression within the inner and outer media, in relation to ILT thickness. Reactive oxygen species control the degradation and remodeling of the extracellular matrix by up‐regulating proteolytic enzymes, such as MMPs. Results showed that oxidative stress and proteolytic enzyme expression were simultaneously, significantly higher within thin thrombus (≤10 mm)‐covered aneurysm wall when compared with the wall covered by thick thrombus (≥25 mm). These findings provide the first demonstration, to our knowledge, of a causative link between oxidative stress instigating proteolytic enzyme expression at the tissue level and human AAA development. Presence of a thin circumferential thrombus should always be considered as a risk factor for the greatest increase in aneurysm growth rate and rupture, giving an indication for surgery timing.—Wiernicki, I., Parafiniuk, M., Kolasa‐Wołosiuk, A., Gutowska, I., Kazimierczak, A., Clark, J., Baranowska‐Bosiacka, I., Szumilowicz, P., Gutowski, P. Relationship between aortic wall oxidative stress/proteolytic enzyme expression and intraluminal thrombus thickness indicates a novel pathomechanism in the progression of human abdominal aortic aneurysm. FASEB J. 33, 885–895 (2019). www.fasebj.org